Global implications of modern enterprise information systems technologies and applications - Gunasekaran, A. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book presents useful strategies, techniques, and tools for the successful design, development, and implementation of enterprise information systems"--Provided by publisher.